The effect of acute Lact-Away supplementation on high-intensity kayak performance - Bonetti, D.; Kilding, A.; Hopkins, W. G. (National Elite Sports Council 2009 Athlete Services Forum - High Performance Programming for Success - 11-12th November - Satellite Program - Applied Physiology Conference 2009 - Australian Institute of Sport, Canberra - 10th, 11th and 13th November, 2009)
Lact-Away is a new orally administered sports supplement claimed by the manufacturer to attenuate blood lactate concentration during exercise and improve performance, but there is limited research on its efficacy. The purpose of this study was to determine the acute effect of Lact-Away supplementation on kayak performance and related physiological measures. Methods Twelve highly-trained kayakers were randomized in a single-blind, crossover fashion to consume either a Lact-Away or a placebo drink prior to performing a maximal incremental exercise test on a wind-braked kayak ergometer, followed 20 min later by a maximal 60-s test. The trials were performed twice in balanced order to improve precision of estimation. Performance measures were peak incremental power, lactate threshold power, heart rate threshold power and mean 60-s power. A 5-point Likert scale was used to obtain measures of gut comfort, wellness and perceived ratings of central and peripheral fatigue. Data were analysed with mixed modelling. Clinical inferences were based on a smallest important change in performance of 1%; an effect was deemed indecisive if benefit was possible (>25% chance) but risk of harm was unacceptable (odds ratio for harm/benefit >1/66). Results Effects of Lact-Away vs placebo were indecisive for measures of peak incremental power (-0.3%; 90% confidence limits, ±1.8%), mean 60-s power (0.8%; ±2.4%), heart-rate profile power (1.0%; ±1.5%) and for ratings of central and peripheral fatigue. Peak lactate concentration was substantially higher after consumption of Lact-Away following the incremental test (5.3%; ±9.4%) and the 60-s test (5.3%; ±9.7%), while lactate-profile power (-1.5%; ±1.9%) and ratings of gut comfort and wellness were decisively lower after consumption of Lact-Away. Discussion/Conclusion The blood lactate response to exercise did not support the manufacturer's claim of a reduction following consumption of Lact-Away. Although some performance outcomes were indecisive, our findings are consistent with no worthwhile enhancement in performance. We do not recommend use of this supplement.